PERAN KEPEMIMPINAN KYAI DALAM MENINGKATKAN MUTU LULUSAN PESANTREN (STUDI KASUS DI PONDOK PESANTREN AL-MUKHLIS CANGKUANG KABUPATEN BANDUNG) - Iwan Mulyanto; Sofyan Sauri; Wiwik Dyah Aryani (JURNAL ILMIAH EDUKATIF, 2022)
Pesantren are madrasas or Islamic educational institutions that teach Islamic values. Pesantren as a non-formal institution has grown from year to year. Today's Islamic boarding schools cannot be underestimated because of their success in producing superior generations during the struggle and today. This research is a qualitative research, with the approach method used is an Explanatory Survey method or a qualitative interactive mode of inquiry, which is an in-depth study using data collection techniques directly from people in their natural environment. The data collection techniques used were observation, interviews, documentation studies and literature studies. The location of this research is Al-Mukhlis Islamic Boarding School, Nagrak Village, Cangkuang District. While the research subjects are Kyai Leadership, students, and asatidz. The results of the study show that there is concrete evidence of the influence of Kyai's leadership on improving the quality of education at Al-Mukhlis Islamic Boarding School. How is the Kyai in carrying out his management, and how is the figure of the Kyai in understanding his interactions with the pesantren community, so that his leadership can improve the quality of education at the Al-Mukhlis Cangkuang Islamic boarding school in Bandung.